INTEGRATED SUPPLY CHAIN SCHEDULING MODELS: A LITERATURE REVIEW - BULKAN, SEROL (My University, 2019)
Research on integration of supply chain and scheduling is relatively recent, andnumber of studies on this topic is increasing. This study provides a comprehensiveliterature survey about Integrated Supply Chain Scheduling (ISCS) models to helpidentify deficiencies in this area. For this purpose, it is thought that this study willcontribute in terms of guiding researchers working in this field. In this study,existing literature on ISCS problems are reviewed and summarized by introducingthe new classification scheme. The studies were categorized by considering thefeatures such as the number of customers (single or multiple), product lifespan(limited or unlimited), order sizes (equal or general), vehicle characteristics(limited/sufficient and homogeneous/heterogeneous), machine configurations andnumber of objective function (single or multi objective). In addition, properties ofmathematical models applied for problems and solution approaches are alsodiscussed.

Bütünleşik Tedarik Zinciri Çizelgeleme (BTZÇ) üzerine yapılan araştırmalar_x000D_ nispeten yenidir ve bu konu üzerine yapılan çalışma sayısı artmaktadır. Bu çalışma,_x000D_ bu alandaki eksiklikleri tespit etmeye yardımcı olmak için BTZÇ modelleri hakkında_x000D_ kapsamlı bir literatür araştırması sunmaktadır. Bu amaçla, bu çalışmanın bu alanda_x000D_ çalışan araştırmacılara rehberlik etmesi açısından katkı sağlayacağı_x000D_ düşünülmektedir. Bu çalışmada, BTZÇ problemleri üzerine mevcut literatür gözden_x000D_ geçirilmiş ve yeni sınıflandırma şeması tanıtılarak çalışmalar özetlenmiştir._x000D_ Çalışmalar; tek veya çoklu müşteri sayısı, sipariş büyüklüğü tipi (eşit veya genel),_x000D_ ürün ömrü (sınırlı veya sınırsız), araç karakteristikleri (sınırlı/yeterli ve_x000D_ homojen/heterojen), makine konfigürasyonları ve amaç fonksiyonu sayısı (tek veya_x000D_ çok amaçlı) gibi özellikler dikkate alınarak kategorize edildi. Ayrıca problemler için_x000D_ uygulanan matematiksel modellerin özellikleri ve çözüm yaklaşımları da_x000D_ tartışılmıştır.
BÜTÜNLEŞİK TEDARİK ZİNCİRİ ÇİZELGELEME MODELLERİ: BİR LİTERATÜR TARAMASI